Economic losses related to internal diseases in Japanese black cattle. (17th August 2015) - Inoue, Keiichi; Honda, Takeshi; Oyama, Kenji
Abstract: The objective of this study was to estimate the direct economic losses due to the condemnation of the liver and large intestine because of internal diseases (multifocal necrosis in the liver (MNL) and inflammation of the large intestine (ILI)), and the indirect losses because of reductions in carcass performance from MNL, bovine abdominal fat necrosis (BFN) and ILI using data from 5383 Japanese Black cattle. Direct losses were estimated by multiplying the price of the condemned part by the frequency of its occurrence owing to the disease. Similarly, indirect losses were estimated as the product of unit carcass price and reduction in carcass weight (CW) due to the disease. The direct impact on the beef cattle industry from MNL and ILI was estimated at around 1.29 million (US1 = ¥120) per year. A least‐squares analysis showed that MNL had no influence on any carcass trait, whereas BFN and ILI significantly reduced CW, rib eye area and darkened the beef. ILI also reduced rib thickness. The indirect losses from BFN and ILI were estimated as a maximum of 131.7 and 256.4 per animal and around 6.26 million and 4.03 million for the industry, respectively, mostly because of the reduction in CW.